Impact of Operative and Peri-operative Factors on the Long-term Prognosis of Primary Liver Cancer Patients Undergoing Hepatectomy - 徐立宁 徐盈盈 高德伟 (Journal of Huazhong University of Science and Technology. Medical sciences, 2016)
This study examined the impact of the operative and peri-operative factors on the long-term prognosis of patients with primary liver cancer undergoing hepatectomy. A total of 222 patients with primary liver cancer who underwent hepatectomy were followed up from January 1986 to December 2010 at Chinese PLA General Hospital. The post-operative complication rate was 14.0% for all cases, 13.7% for hepatocellular carcinoma（HCC）, 10.0% for cholangiocarcinoma. The 1-, 3-, 5- and 10-year overall survival rates in patients with primary liver cancer after resection were 76.6%, 57.6%, 41.4%, and 21.0%. The survival rates were significantly higher in the HCC group than in the cholangiocarcinoma group（P=0.000）, in the non-anatomical resection group than in the anatomical resection group（P=0.005）, in the female group than in the male group（P=0.002）, in patients receiving no blood transfusion than in those who were given intra-operative blood transfusion（P=0.000）, in patients whose intra-operative blood loss was less than 400 m L than in those who intra-operatively lost more than 400 m L（P=0.000）. No significant difference was found in the survival rate between the HBs Ag-positive group and the HBs Ag-negative group（P=0.532）. Our study showed that anatomical resection, blood loss and blood transfusion were predictors of poor survival after hepatectomy for primary liver cancer patients, and concomitant hepatitis B virus infection bore no relation with the post-resection survival.